Prevalence of malocclusion, oral parafunctions and temporomandibular disorder‐pain in Italian schoolchildren: An epidemiological study. (7th May 2019) - Perrotta, Stefania; Bucci, Rosaria; Simeon, Vittorio; Martina, Stefano; Michelotti, Ambra; Valletta, Rosa
Abstract: Background: The prevalence of malocclusion, temporomandibular disorders (TMD) and oral parafunctions is highly debated in children population. Objectives: To investigate the prevalence of malocclusion, self‐reported oral parafunctions and TMD‐pain in Italian schoolchildren and to assess the association between the examined factors. Methods: A total of 700 children aged 9‐11 years were selected among six public schools in Campania region (Italy). Molar relationship, overjet, overbite and cross‐bite were assessed through a clinical examination. Furthermore, the subjects were demanded to fill in a validated questionnaire for TMD‐pain screening and the short form of the Oral Behaviours Checklist. Descriptive statistics were used to report the frequencies. The associations between occlusal traits, oral parafunctions and TMD‐pain were analysed with a Pearson chi‐square test, as expressed by odds ratio and 95% confidence intervals. The significance level was set at P  < 0.05. Results: Molar Class I was the most frequently encountered molar relationship, followed by molar Class II, subdivision and molar Class III. Increased overjet was more common than negative overjet. Posterior cross‐bite was observed in 12% of children. TMD‐pain was recorded in 14.7% of subjects. High frequency of oral parafunctions was reported in 21.3% of subjects. A significant association was found between TMD‐pain and negative overbite. Cross‐bite and high frequency of oral parafunctions were associated with TMD‐pain. Conclusion: The current results show that malocclusion, self‐reported oral parafunctions and TMD‐pain are frequent findings among Italian schoolchildren and that some occlusal factors and high frequency of oral parafunctions might be associated with TMD‐pain.